International Lung Cancer Consortium: Coordinated association study of 10 potential lung cancer susceptibility variants - Truong, Thérèse; Sauter, Wiebke; McKay, James D.; Hosgood, H.Dean, III; Gallagher, Carla; Amos, Christopher I.; Spitz, Margaret; Muscat, Joshua; Lazarus, Philip; Illig, Thomas; Wichmann, H.Erich; Bickeböller, Heike; et al. (Carcinogenesis, 2010)
Background . Analysis of candidate genes in individual studies has had only limited success in identifying particular gene variants that are conclusively associated with lung cancer risk. In the International Lung Cancer Consortium (ILCCO), we conducted a coordinated genotyping study of 10 common variants selected because of their prior evidence of an association with lung cancer. These variants belonged to candidate genes from different cancer-related pathways including inflammation ( IL1B ), folate metabolism ( MTHFR ), regulatory function ( AKAP9 and CAMKK1 ), cell adhesion ( SEZL6 ) and apoptosis ( FAS , FASL , TP53 , TP53BP1 and BAT3 ). Methods. Genotype data from 15 ILCCO case-control studies were available for a total of 8431 lung cancer cases and 11 072 controls of European descent and Asian ethnic groups. Unconditional logistic regression was used to model the association between each variant and lung cancer risk. Results . Only the association between a non-synonymous variant of TP53BP1 (rs560191) and lung cancer risk was significant (OR = 0.91, P  = 0.002). This association was more striking for squamous cell carcinoma (OR = 0.86, P  = 6 × 10 −4 ). No heterogeneity by center, ethnicity, smoking status, age group or sex was observed. In order to confirm this association, we included results for this variant from a set of independent studies (9966 cases/11 722 controls) and we reported similar results. When combining all these studies together, we reported an overall OR = 0.93 (0.89-0.97) ( P  = 0.001). This association was significant only for squamous cell carcinoma [OR = 0.89 (0.85-0.95), P  = 1 × 10 −4 ]. Conclusion. This study suggests that rs560191 is associated to lung cancer risk and further highlights the value of consortia in replicating or refuting published genetic associations.